POSITRON EMISSION TOMOGRAPHY IN PATIENTS WITH DRUG RESISTANT TEMPORAL LOBE EPILEPSY WITH DIFFERENT ICTAL PROPAGATION PATTERNS IN SCALP EEG - Nermin Görkem Şirin İnan; Bedia Samancı; Ebru Yılmaz; Ayşen Zehra Gökyiğit; Betül Baykan; Rabia Candan Gürses; Nerses Bebek (İstanbul Tıp Fakültesi Dergisi)
Objective: In presurgical evaluation, positron emission tomography with fluorodeoxyglucose-F18 (FDG-PET) is an important tool in identifying epileptogenic area. The aim of this study was to evaluate glucose metabolism in FDG-PET in patients with temporal lobe epilepsy (TLE) showing ‘switch-of lateralisation’ (SL) and ‘bilateral asynchrony’ (BA) in ictal scalp EEG and compare their results with patients with TLE and none of these patterns. Methods: Twenty-four patients with TLE showing SL and/or BA in at least one of their seizures in video-EEG monitoring and 38 patients with TLE and without these patterns who had epilepsy surgery and a follow-up at least 5-years were included. The clinical, electrophysiological and imaging features were evaluated and a statistical comparison was performed between the groups. Results: Bilateral hypometabolism was more frequent in patients with SL and/or BA (39%) than in patients without these patterns (0%, p=0.040) in parallel with bilateral interictal epileptiform discharges and bilateral abnormalities in MRI. The presence of unilateral or bilateral hypometabolism was not related to postsurgical outcome in patients with SL and/or BA. Conclusion: The possibility of low accuracy in the lateralisation of hypometabolism in FDG-PET might be interpreted cautiously in TLE with bilateral independent ictal activity like SL and BA.